Preparation, characterization and adsorption studies of heavy metals onto activated adsorbent materials derived from agricultural residues / Zaira Zaman Chowdhury - Chowdhury, Zaira Zaman (2013)
The extensive use of commercial activated carbon as an adsorbent for the purification of industrial effluent is not economically feasible due its high operational cost. Therefore, this research has been undertaken to explore the potential of certain agro based residues to produce suitable adsorbent for scavenging divalent cations of lead (Pb), copper (Cu) and manganese (Mn) from waste water to meet specific industrial requirements. In this regard, powdered activated carbons (PAC) were produced from cellulosic precursors namely kenaf core (KC) and kenaf fiber (KF) and granular activated carbon (GAC) from mangostene fruit shell (MFS) by physio-chemical activation. Their performance of the prepared activated carbons (KCAC, KFAC and MFSAC) was compared with activated oil palm ash (AOPA) sample in batch sorption system. Design of experiment (DOE) based on central composite design (CCD) was used to study the effect of activation temperature, time and impregnation ration (IR) on adsorption performance along with maximum possible yield for powered activated carbon (PAC) from KC and KF. The results demonstrated that the optimum condition to obtain highest removal percentage and yield were different depending on the characteristics of the raw materials and the adsorbate under investigation. MFS was used to prepare granular activated carbon (GAC) due to its hard texture. It was used for batch as well as fixed bed sorption system. The adsorption mechanisms of activated carbon and activated oil palm ash towards the divalent cations used for this study were completely different. This is expected owing to their different inherent surface morphological features. To prepare activated adsorbent iii (AOPA) from natural oil palm ash (OPA), activation reaction by using sodium hydroxide has been carried out by using predefined reaction condition of temperature, time and impregnation ratio (IR) suggested by the software (DOE). The surface characteristics of these powdered and granular adsorbent were determined in terms of their BET surface area, FTIR analysis, SEM analysis, bulk density and iodine number measurement. Chemical composition of activated carbons (KCAC, KFAC and MFSAC) were analyzed by ultimate (C, H, N, others) and proximate analysis (C, moisture volatile materials and ash). X-ray analysis (XRF) analysis was carried out to determine the chemical constituents of natural oil palm ash (OPA) and activated palm ash (AOPA). The effect of initial metal ion concentration (50- 100 mg/l), contact time, pH of the solution and temperature (30 °C, 50 °C and 70 °C) were determined in this work. Equilibrium data were further analyzed to evaluate kinetics, isotherm and thermodynamic behavior of the adsorbate - adsorbent system. The fixed bed column showed better performance with lower influent concentration, less flow rate of the influent and higher bed height of the adsorbent. Desorption by using mineral acid was suitable for regenerating the spent adsorbent for further use. It can be concluded that the overall performance of the prepared activated carbons are better than the activated ash sample.